Physical Activity Guidelines for and the Present State of Health Promotion: A Comparison of New Zealand and Japan - Sakai, H; Hume, P (成蹊大学, 2015)
In this study, we attempted to compare physical activity guidelines established by Japan and New Zealand based on the World Health Organization Global Recommendations on Physical Activity for Health. We compared documents and websites published by the New Zealand Ministry of Health with those published by the Ministry of Health, Labour and Welfare in Japan. Results revealed that standards were not set for 5–17-year-olds and that only the main points were briefly summarized for other age groups in Japan's guidelines. It was clear that other ministries and associations were publishing the details from their respective standpoints. We were unable to compare current levels of physical activity closely because while physical activity in general is surveyed in New Zealand, Japan only collects data on exercise included in physical activity. Because the international trend is to use level of physical activity as a standard, this suggests that going forward, Japan needs to collect data on physical activity and promote devices that can measure physical activity more closely. We also noted attempts to raise public awareness from the standpoint of citizens, such as through New Zealand's “Green Prescription,” Japan's “Plus 10” and the dissemination of information via Facebook．